Rent-a-pal [videorecording (DVD)] - Wheaton, Wil; Folkins, Brian Landis; Rutledge, Amy; Brady, Kathleen (Scream Factory, 2021)
Set in 1990, a lonely bachelor named David searches for an escape from the day-to-day drudgery of caring for his aging mother. While seeking a partner through a video dating service, he discovers a strange VHS tape called Rent-A-Pal. Hosted by the charming and charismatic Andy, the tape offers him much-needed company, compassion, and friendship. But, Andy's friendship comes at a cost, and David desperately struggles to afford the price of admission.